(untitled) (Research, Society and Development, 2022)
The development of family farming from an agroecological perspective is an alternative for sustainable agricultural production. These are agroecosystems that act positively for food security and sovereignty, although they have resource constraints, which are a challenge for their livelihoods. As for the objective, in this study, aspects related to the performance of agroecological family farming, applied to a Brazilian context, were evaluated. More specifically, the socioeconomic development and dynamics of livelihood strategies were analyzed. The work was based on case studies, exploring empirical evidence in three agroecosystems located in the northeast region of Brazil. Data were obtained through interactional methods and systematic observations, involving a multidisciplinary team with the active participation of farmers. The results pointed to the need to financially leverage agroecologically-based family farmers, in order to enable the development of an alternative for sustainable production. In addition, an agricultural context was identified with few resources and several restrictions, but in which farmers resist and persist in the use of agroecological practices. Finally, approaches that seek to understand the reality of farmers, pointing out socioeconomic indicators and livelihood strategies, can be a basis for the efficient performance of organizations and the elaboration of public policies that seek to promote sustainable agriculture.